Formulasi Sediaan Krim Antiinflamasi Ekstrak Etanol Daun Rambusa (Passiflora foetida L) - Evi Mulyani; Halida Suryadini; Rizka Rahmadina Putri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Rambusa (Passiflora foetida L) is a medicinal plant that is widely found in various regions in Indonesia, including in Central Kalimantan. Rambusa is empirically used as an antibacterial and anti-inflammatory. Previous research has shown that the content of Rambusa (Passiflora foetida Linn) leaves from Central Kalimantan is one of the steroids which has anti-inflammatory properties. The purpose of this study was to determine whether the ethanol extract of rambusa leaves can be processed into anti-inflammatory cream preparations and to determine the results of physical tests, namely organoleptic tests, homogeneity tests, dispersibility tests, and pH tests. This research was conducted by the smelting method. The results showed that the three creams of ethanol extract of rambusa leaf (Passiflora foetida L) had met the requirements for physical properties of homogeneity, spreadability, and pH.